Evolution of the angiosperm ionome with reference to the Caryophyllales order - Neugebauer, Konrad (2020)
The ionome is the elemental composition of a living organism, its tissues, cells or cell compartments. It includes both essential and nonessential elements in whatever chemical form they occur. The ionomes of most angiosperm species have not been defined and the evolution of angiosperm ionomes has not been studied in any detail. To provide a comprehensive understanding of the variation in the ionome as many angiosperm species as possible must be compared. To reveal the genetic component of the variation in the angiosperm ionome, plants should be grown under similar conditions to minimise environmental effects. This thesis (1) describes and compares the ionomes of whole plants and individual organs of angiosperm species grown hydroponically, (2) tests the correlations between ionomes of angiosperm taxa and their phylogenetic relationships, and (3) tests associations of ionome traits with selected phenotypic traits. It places particular emphasis on the Caryophyllales order because species of this order were previously shown to accumulate abnormally large concentrations of mineral elements in their shoots. The ionomes of (1) shoots of 35 angiosperm orders represented by 334 species from 79 families, (2) shoots and roots of 13 Caryophyllales families represented by 45 species, and (3) roots, stems and leaves of 14 native Brazilian forest species representing 14 genera, nine families, and seven angiosperm orders were defined. It was tested whether (1) angiosperm clades could be distinguished by their plant and organ ionomes, (2) the concentrations of mineral elements in shoots were correlated across angiosperm orders, (3) shoot and root ionomes differed, and (4) organ ionomes of angiosperm taxa were associated with their phylogenetic relationships. Angiosperm orders could be distinguished by their shoot ionomes, Caryophyllales families and species could be distinguished by their shoot or root ionomes, and the 14 Brazilian forest species could be distinguished by their whole plant ionomes or by their root, stem or leaf ionomes. The ionomes of different organs of angiosperms were distinct and differences between the shoot and root ionomes were greater than differences in the ionomes of an organ among species. The organ ionomes of angiosperm taxa were not associated with phylogenetic relationships. Among angiosperm orders, (1) the commelinid monocot orders were characterised by small shoot Ca and Mg concentrations, which was attributed to their cell wall chemistry, (2) Brassicales had large shoot S concentrations, which was attributed to their biosynthesis of glucosinolates, and (3) Caryophyllales were distinguished by large shoot Mg and Na concentrations. There were strong positive correlations between shoot N, P and K concentrations, between shoot Ca and Mg concentrations, and between shoot Mn, Cu and Zn concentrations. It was observed that an abnormally large shoot Na concentration ([Na]shoot) had evolved several times within the Caryophyllales order, predominantly in the Aizoaceae and Amaranthaceae families, and that only species with abnormally large [Na]shoot had [Na]shoot/[Na]root quotients greater than unity. The shoot and root ionomes clustered differently among Caryophyllales families and neither were correlated with phylogeny. Similarly, organ ionomes clustered differently among the 14 Brazilian species studied and none were associated with phylogenetic relationships or successional ecology. These observations can be explained by convergent evolution of traits determining the ionome of an organ in distantly related angiosperm taxa.